2020
DOI: 10.3390/ijerph17020538
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Sweet and Fatty Taste in Children and Their Mothers in Association with Weight Status

Abstract: Strong preferences for sweet and fat tastes (characters) are associated with the consumption of foods high in calories. The taste preferences, especially the sweet and fat tastes (characters), might be one of the factors predisposing children to become overweight and/or develop obesity. The aim of the study is to assess taste preferences in children and their mothers in association with their weight status. In the study, 150 children aged 8–15 were included; among them, 75 had overweight and/or obesity, and 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…The present study revealed that 4- to 6-year-olds have a clear preference for sweet-tasting foods, are familiar with a larger number of sweet-tasting foods and dishes, and are less likely to dislike these items. According to Mennella [ 53 ], Lanfer [ 20 ] and Sobek [ 24 ], children prefer sweetened products such as breakfast cereals, juice, soft drinks, sweets and puddings. The present study also demonstrated that children enjoyed fruit which is naturally sweet, and that their preference for fatty taste, in particular fast foods, increased with age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study revealed that 4- to 6-year-olds have a clear preference for sweet-tasting foods, are familiar with a larger number of sweet-tasting foods and dishes, and are less likely to dislike these items. According to Mennella [ 53 ], Lanfer [ 20 ] and Sobek [ 24 ], children prefer sweetened products such as breakfast cereals, juice, soft drinks, sweets and puddings. The present study also demonstrated that children enjoyed fruit which is naturally sweet, and that their preference for fatty taste, in particular fast foods, increased with age.…”
Section: Discussionmentioning
confidence: 99%
“…Food preferences, especially for sweet and fatty taste, and the consumption of sugar-sweetened beverages (SSBs) could be strong risk factors for increased weight and/or obesity in children [ 24 , 25 ]. Children who consumed SSBs during infancy had higher odds of obesity at 6 years than non-SSB consumers [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It corresponds with the fact that in our own study, the ‘hedonists’ cluster more often declared buying pastries or cakes than two other clusters, both in the female and male subgroups. Such behavior may adversely influence their body weight, as in the study of Sobek et al [ 39 ], it was found that in a group of children and adolescents who preferred the high-sweet taste, the frequency of obesity was twice as high as in a group of individuals with the low-sweet taste preference. Regardless of the gender, the ‘hedonists’ cluster along with the ‘high-preferring’ cluster showed also a high consumption of cream, as the majority of the respondents declared that they often have cream on desserts.…”
Section: Discussionmentioning
confidence: 99%
“…Early experiences with different tastes shape the acquired preferences which are important for the later acceptance of food, especially healthy food. Available studies show that proper nutrition of mothers during pregnancy, lactation, and in the first years of the child's life not only ensures adequate weight gain and optimal nutritional status, but also influences the long-term effects of the so-called health 'programming' of the metabolism, conditioning proper future health, also of the oral cavity [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Improper nutritional behaviors in children change throughout their individual lives, but also have wide-ranging consequences, from behavioral problems related to anorexia, overeating, or nutritional neophobia, to significant health problems such as increased risk of obesity, endocrine problems, anemia, idiopathic shortness of growth, cardiovascular diseases, type 2 diabetes mellitus (T2DM), and other metabolic disorders and ECC [ 4 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. A strong correlation has been proven between excessive sugar supply with the risk of caries [ 24 ], which is considered a social disease of a progressive nature, affecting people of all ages all over the world and which is considered the most common infectious disease among children [ 25 ].…”
Section: Introductionmentioning
confidence: 99%